The Golden Triangle (India-China-Indonesia) Maritime Cultural Relations (A Critical Analysis on Kitab ‘Ajaib al-Hind by Buzurg Ibn Shahriyār (d.399 H/1009 M) - Nanang Nurcholis (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Historically the Golden Triangle (India-China-Indonesia) has been engaged in sea journeys since very early times. The Indian Ocean in fact unified the maritime culture of seafarers and merchants belonging to Arabian, Persian, Indian, East African backgrounds, and even from Southeast Asia though socially and ethnically diverse. The early maritime cultural ties of India-China-Indonesia might be traced back in Kitab ‘Ajaib al-Hind by the Persian sea captain Buzurg Ibn Shahriyār (d.399/1009). It is one of the earliest Arabic tales dealing mainly with the Indian Ocean i.e. from East Africa to China, the Arabian-Persian Gulf and the Red Sea. Additionally, it also tells us the navigation activities in Malay region especially in Indonesia. The study conducts an analysis of maritime life in the Western Indian Ocean as portrayed in the mariners’ tales of Buzurg b. Shahriyār. Having selected the terminology as found in Kitab Aja’ib al-Hind and conducting synchronic investigation, the analysis will run as follows: a) the textual reference from which the term has been extracted; b) a translation of the passage containing the term; c) a brief summary of the context of the passage, and d) a discussion of the term in question. Finally, this study establishes some proofs of India-China-Indonesia maritime relations since very ancient times. Key words: al-hind, al-sin, suvarnabhumi, sumatra